Psychometric properties for the General Procrastination Scale (GPS) Brazilian version - Guilherme Chirinéa; André Pereira Gonçalves; Villena Louise Meira Costa Lima; Ana Luísa Menezes Santos; Cecília Pires de Almeida; Pragya Lodha (Estudos de Psicologia (Campinas))
Abstract Objective Procrastination has been the subject of studies due to its impact on people’s lives, work performance, satisfaction, and mental health. Measuring this construct is necessary to understand daily life’s direct and indirect effects. The objective of this study was to verify the evidence of validity and reliability of the General Procrastination Scale for the Brazilian context as a method of investigating the phenomenon. Method Data were collected from 421 adults, aged between 18 and 64 years and with complete primary education, based on the application of a self-report measurement questionnaire. Results The results indicated a unifactorial structure and expected correlations with the external measures. Conclusion These results demonstrate the suitability of the scale for measuring procrastination in a Brazilian sample, which places this scale as a possibility of use in research to measure this construct.